Temporal Dynamics of Anti–Type 1 Interferon Autoantibodies in Patients With Coronavirus Disease 2019. (7th December 2021) - Shaw, Elana R; Rosen, Lindsey B; Cheng, Aristine; Dobbs, Kerry; Delmonte, Ottavia M; Ferré, Elise M N; Schmitt, Monica M; Imberti, Luisa; Quaresima, Virginia; Lionakis, Michail S; Notarangelo, Luigi D; Holland, Steven M; et al.
Abstract: Binding levels and neutralization activity of anti–type 1 interferon autoantibodies peaked during acute coronavirus disease 2019 and markedly decreased thereafter. Most patients maintained some ability to neutralize type 1 interferon into convalescence despite lower levels of binding immunoglobulin G. Identifying these autoantibodies in healthy individuals before the development of critical viral disease may be challenging.